Effects of γ-Irradiation of Wild Thyme (Thymus serpyllum L.) on the Phenolic Compounds Profile of Its Ethanolic Extract - Janiak Michał A.; Slavova-Kazakova Adriana; Kancheva Vessela D.; Ivanova Milena; Tsrunchev Tsvetelin; Karamać Magdalena (Polish Journal of Food and Nutrition Sciences)
The presented study revealed that there were changes in the phenolic compounds profile of extract of wild thyme (Thymus serpyllum L.) after γ-irradiation at the dose of 5 kGy. Ethanolic extracts of irradiated and non-irradiated herb were prepared and their compounds were analyzed by RP-HPLC-DAD technique. Between thirty two detected constituents, twelve phenolic compounds classified as hydroxybenzoic and hydroxycinnamic acids derivatives, flavones and flavanones were identified. Among them, caffeic acid derivatives and flavones predominated with the highest content of rosmarinic acid and luteolin-7-O-glucoside, respectively. Additionally, thymol was recognized in the analyzed extracts. γ-Irradiation slightly affected the quantitative profile of phenolic compounds of a wild thyme ethanolic extract. Only four constituents differed significantly (P<0.05) in terms of their content in the irradiated and non-irradiated samples. The content of phenolic acids (p-coumaric and caffeic acids) decreased and that of flavonoid aglycons (luteolin and eriodictyol) increased after the γ-ray treatment.